2006
DOI: 10.1148/radiol.2383041825
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastases: Detection with Multi–Detector Row CT, SPIO-enhanced MR Imaging, and Both Techniques Combined

Abstract: The addition of SPIO-enhanced MR imaging to contrast-enhanced multi-detector row CT (ie, combined analysis of SPIO-enhanced MR images and contrast-enhanced CT images) can improve sensitivity in the detection of hepatic metastases, although this improvement in sensitivity was not significant at AFROC analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
4
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 23 publications
1
30
4
2
Order By: Relevance
“…SPIOand Gd-EOB-DTPA-enhanced MR images are used to improve detection and characterization of focal hepatic lesions in clinical studies. 9,10 On SPIO-enhanced MR imaging, we visualized the present BDA as an area of diminished SPIO uptake, such as that observed in hepatic metastatic lesions. During the hepatobiliary phase of Gd-EOB-DTPA-enhanced MR imaging, our case and one previously reported case 5 demonstrated distinct hypointensity.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 90%
“…SPIOand Gd-EOB-DTPA-enhanced MR images are used to improve detection and characterization of focal hepatic lesions in clinical studies. 9,10 On SPIO-enhanced MR imaging, we visualized the present BDA as an area of diminished SPIO uptake, such as that observed in hepatic metastatic lesions. During the hepatobiliary phase of Gd-EOB-DTPA-enhanced MR imaging, our case and one previously reported case 5 demonstrated distinct hypointensity.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 90%
“…However, magnetic resonance imaging (MRI) has improved markedly, especially in combination with new contrast agents [10,11,14]. Constant developments in liver imaging have resulted in many trials assessing the optimal imaging strategy, but contradictory results have been reported [11,12,13,14,15,16,17]. Currently, there is no uniform recommendation for the use of either MSCT or MRI for evaluation of CRLM in patients who did not receive NAC.…”
Section: Introductionmentioning
confidence: 99%
“…CT should be performed with native images as well as after using modern nonionic, iodine-containing water-soluble contrast agents; multidetector helical CT is today's standard [24][25][26][27] . For helical CT, 5 mm reconstructions should be used allowing a minimum-sized lesion of 10 mm to be detected.…”
Section: Reviewmentioning
confidence: 99%
“…Multisplice spiral CT has a sensitivity for the detection of liver metastasis of 65-85% [24][25][26][27] , thus making it the method of choice for staging urogenital cancer. Contrastenhanced MRI increases the sensitivity for detecting metastases to 90% as compared to only 70% of unenhanced MRI [26,27] .…”
Section: Reviewmentioning
confidence: 99%